2015 IEEE Global Communications Conference (GLOBECOM) 2014
DOI: 10.1109/glocom.2014.7417541
|View full text |Cite
|
Sign up to set email alerts
|

Soft Input Soft Output MMSE-SQRD Based Turbo Equalization for MIMO-OFDM Systems under Imperfect Channel Estimation

Abstract: In this paper, a turbo equalization scheme for MIMO-OFDM systems under imperfect channel estimation based on soft-input soft-output (SISO) minimum mean-square error (MMSE) sorted QR decomposition (SQRD) is proposed. A turbo structure consists of a SISO detector and a SISO decoder where extrinsic information is exchanged between the two SISO modules. Turbo equalization schemes are preferable in practical communication systems due to their good performance and acceptable computational complexity. MMSE-SQRD based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Multiple‐input multiple‐output (MIMO) systems have the advantages of high spectrum and energy efficiency due to the spacial diversity and multiplexing gain over single antenna systems [1–13]. MIMO techniques have been successfully applied to current mobile cellular networks [6–8], underwater acoustic communication systems [9, 10], and vehicular communications [11]. By extending the MIMO system from a small scale to a large scale, the potential spectrum and energy efficiency can be boosted in orders of magnitude [14–18].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple‐input multiple‐output (MIMO) systems have the advantages of high spectrum and energy efficiency due to the spacial diversity and multiplexing gain over single antenna systems [1–13]. MIMO techniques have been successfully applied to current mobile cellular networks [6–8], underwater acoustic communication systems [9, 10], and vehicular communications [11]. By extending the MIMO system from a small scale to a large scale, the potential spectrum and energy efficiency can be boosted in orders of magnitude [14–18].…”
Section: Introductionmentioning
confidence: 99%
“…The employment of turbo processing techniques in MIMO systems has been well investigated. It has also been demonstrated that with iterative processing, a simple equaliser can eventually approach the system bit error rate (BER) performance of the optimal equalisers [1, 2, 6–10, 19–28]. Therefore, most studies have focused on the design of low complexity and fast convergence turbo equaliszers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations